Implementasi Algoritma Alpha Beta Pada Aplikasi Pembelajaran Untuk Anak Usia Dini Berbasis Android - Angga Rahma Zagitha Siregar; Siti sundari; Sumi Khairani (SNASTIKOM, 2022)
The use of media in the learning process is one of the efforts to create more meaningful and quality learning. Learning media serves as a tool to convey learning messages. Learning media must be packaged as attractively as possible so that early childhood can be interested in learning an introduction to material and the learning process only uses conventional media such as blackboards, textbooks. This kind of learning is less interactive, as a result, early childhood does not understand the material well and affects their learning outcomes. This research will build a learning game for word, letter and image recognition, this game is aimed at children aged 1-10 years and this game was developed using Unity 3D software and the use of flow diagrams of a unified modeling language to maximize the workflow of the number recognition game. , letters and images. The purpose of this research is to produce an application that can be used for android based children